Faktor-Faktor Pemicu Minat Mahasiswa Menjadi Wirausaha (Studi Empiris di Universitas Hindu Indonesia) - Ni Made Wisni Arie Pramuki; Komang Ary Pratiwi; Putu Atim Purwaningrat (Ekuitas: Jurnal Pendidikan Ekonomi, 2019)
Students participate actively in the development of the nation with a hope not only as job seekers, but also as providers or creators of employment by becoming entrepreneurs. Entrepreneurship entry into the college curriculum is expected to provide graduate competencies with hardskills and entrepreneurial softskills. But the low interest of students to become entrepreneurs is the motivation and attractiveness of researchers to conduct further studies. Thus, it is very important to know what factors can encourage students as triggers to become entrepreneurs. This research was carried out with the aim to identify factors that could trigger entrepreneurial interest in students, especially at the Faculty of Economics, Indonesian Hindu University. The analysis was carried out on the data obtained from the primary data by using questionnaire instruments to 100 students which included factor analysis and regression analysis. Factor analysis test results obtained evidence that the main factors that can trigger student interest into entrepreneurship can be grouped into three factors, namely attitudes, image and financial motivation. While the regression analysis obtained evidence that the three factors namely attitudes, image and financial motivation have a positive and significant influence on the interest of students to become entrepreneurs. Thus awareness programs for entrepreneurship need to be carried out more efficiently and effectively, so that our next generation is more as a creator of employment than a job seeker.